Quantitative changes in mental health measures with 3MDR treatment for Canadian military members and veterans. Issue 8 (18th July 2022) - Jones, Chelsea; Smith‐MacDonald, Lorraine; Brown, Matthew Robert Graham; Pike, Ashley; Vermetten, Eric; Brémault‐Phillips, Suzette
Abstract: Objective: Military members and veterans are at elevated risk of treatment‐resistant posttraumatic stress disorder (TR‐PTSD) due to higher rates of exposure to potentially traumatic events during the course of duty. Knowledge of TR‐PTSD is limited, and specific protocols or evidence‐based TR‐PTSD therapies are lacking. Multimodal motion‐assisted memory desensitization and reconsolidation (3MDR) therapy is an emerging intervention for combat‐related TR‐PTSD. The purpose of this study was to preliminarily assess the effectiveness of 3MDR in addressing TR‐PTSD in Canadian military members and veterans. Methods: This study is a longitudinal mixed‐methods clinical trial. English‐speaking military members and veterans aged 18–60 with TR‐PTSD were recruited to participate. The intervention consisted of six sessions of 3MDR therapy. Quantitative data were collected pretreatment, posttreatment, and longitudinally at 1, 3, and 6 months after completion of 3MDR. Results: Results from the first 11 participants to complete the 3MDR protocol exhibited statistically significant improvement (surviving multiple comparison correction) in clinically administered and self‐reported scores for PTSD (CAPS‐5 and PCL‐5), moral injury (MISS‐M‐SF), depression (PHQ‐9), anxiety (GAD‐7), emotional regulation (DERS‐18), and resilience (CD‐RS‐25). Conclusion: The preliminary and exploratory results from this clinical trial support the growing body of literature illustrating 3MDR as an effective treatment for military‐related TR‐PTSD. These results are notable given participants' previous lack of success with frontline psychotherapeutic and pharmacological interventions. Given that there are currently very limited treatment options for TR‐PTSD, 3MDR could prove to be a valuable treatment option for military members and veterans with TR‐PTSD. Abstract :